Reconsidering prospect theory in health communication: interplay of certainty with different types of framing - Lee, Tae Kyoung (2024)
While framing studies in health communication research are grounded in prospect theory, there are deviations from the original prospect theory in three major areas: (1) the conceptualization of risk as susceptibility/severity rather than certainty, (2) the presentation of outcomes of different events in gain- and loss-framed messages rather than different aspects of the same outcome, and (3) the use of participants’ ratings as outcome variables instead of participants’ choice of one option over the other. To understand the implications of these discrepancies, two randomized experiments were conducted within the context of obesity policy support. In experiment 1, participants were asked to rate their support for policies. With a framing approach consistent with prospect theory (called prospect-theory framing in this study), participants’ ratings were marginally significant but in a consistent pattern with prospect theory; however, no effect was found with the framing approach described in health communication literature (called persuasion framing in this study). In Study 2, participants were asked to choose one policy for obesity over the other, revealing a result aligning with the prospect theory predictions. These findings underscore the influence of both framing conceptualization and outcome measurement on observed framing effects.